Prevention of polyglutamine oligomerization and neurodegeneration by the peptide inhibitor QBP1 in Drosophila. - Nagai, Y.; Fujikake, N.; Ohno, K.; Higashiyama, H.; Popiel, H.A.; Rahadian, J.; Yamaguchi, M.; Strittmatter, W.J.; Burke, J.R.; Toda, T. (Human Molecular Genetics, 2003)
Polyglutamine (polyQ) diseases are a growing class of inherited neurodegenerative diseases including Huntington's disease, which are caused by abnormal expansions of the polyQ stretch in each unrelated disease protein. The expanded polyQ stretch is thought to confer toxic properties on the disease proteins through alteration of their conformation leading to pathogenic protein-protein interactions including oligomerization and/or aggregation. Hypothesizing that molecules with selective binding affinity to the expanded polyQ stretch may interfere with the pathogenic properties, we previously identified Polyglutamine Binding Peptide 1 (QBP1) from combinatorial peptide phage display libraries. We show here that a tandem repeat of the inhibitor peptide QBP1, (QBP1)(2), significantly suppresses polyQ aggregation and polyQ-induced neurodegeneration in the compound eye of Drosophila polyQ disease models, which express the expanded polyQ protein under the eye specific promoter. Most importantly, (QBP1)(2) expression dramatically rescues premature death of flies expressing the expanded polyQ protein in the nervous system, resulting in the dramatic increase of the median life span from 5.5 to 52 days. These results suggest that QBP1 can prevent polyQ-induced neurodegeneration in vivo. We propose that QBP1 prevents polyQ oligomerization and/or aggregation either by altering the toxic conformation of the expanded polyQ stretch, or by simply competing with the expanded polyQ stretches for binding to other expanded polyQ proteins. The peptide inhibitor QBP1 is a promising candidate with great potential as a therapeutic molecule against the currently untreatable polyQ diseases.